A Study of Utilization of Antimicrobial Agents in Patients on Ventilator in Intensive Care Unit (Icu) at Tertiary Care Teaching Hospital, India - Prakash R Shelat; Anuradha M Gandhi; Prakruti P Patel (Journal of Clinical and Diagnostic Research, 2014)
Objective: To study the use of antimicrobial agents in patients on ventilator in ICU. Materials and Methods: Study was conducted at tertiary care teaching hospital Ahmedabad, India. Total 300 patients admitted in ICU and prescribed antimicrobial agents were included in the study. The data were recorded in preformed Case Record Form (CRF) and were analysed by Z and x2 Test. Results: Patients were divided into group A (patients on ventilator support) and group B (patients without ventilator support). In all the patients antimicrobial agents were prescribed empirically and more than two antimicrobial agents were prescribed in both groups. It was observed that above 60% antimicrobial agents were prescribed according to WHO, National and State Essential Medicine List (EML). Restricted antimicrobial agents (according to antimicrobial policy of tertiary care teaching hospital) were prescribed significantly (p<0.05) higher in group A as compared to group B. Resistance to antimicrobial agents by Pseudomonas aeruginosa and Kleibsella shown significantly (p<0.05) higher in group A as compared to group B. Change of antimicrobial therapy after Culture Sensitivity Test (CST) was significantly (p<0.05) higher in group A as compared to group B Conclusion: Number of antimicrobial agents, antimicrobial resistance and change of antimicrobial therapy after CST were higher in patients on ventilator support.